Is bariatric surgery the answer to urinary incontinence in obese women?. Issue 1 (16th October 2015) - Shimonov, Mordechai; Groutz, Asnat; Schachter, Pinhas; Gordon, David
Abstract : Aims: To investigate the effect of bariatric surgery on female pelvic floor disorders. Methods: Eighty consecutive obese women who underwent a laparoscopic sleeve gastrectomy were prospectively enrolled. Four validated questionnaires (ICIQ‐UI, BFLUTS‐SF, PFDI‐20, PISQ‐12) were used to evaluate pelvic floor symptoms before and 6 months after surgery. Outcome results were analyzed according to the presence of preoperative urinary incontinence (UI), defined as a positive answer to the question "how often do you leak urine?" on the ICIQ‐UI questionnaire. Results: Seventy‐seven women (age 41.3 ± 11.5 years; parity 1.9 ± 1.6) completed all pre‐ and postoperative questionnaires. Mean body mass index (BMI) before and 6 months after surgery was 42 ± 4.7 and 33 ± 4.7, respectively. Preoperatively, 29 (37.7%) women (mean age 45.6 ± 11, mean BMI 42.3 ± 5.2) had UI, 17 (59%) of whom had stress urinary incontinence. Surgically induced weight loss was associated with statistically significant improvement in UI and filling symptoms, pelvic organ prolapse and colorectal‐anal scores, and condition‐specific sexual function and quality of life parameters. Specifically, the total score of the ICIQ‐UI questionnaire decreased from 9.28 ± 3.6 preoperatively to 2.9 ± 3.8 postoperatively ( P  < 0.001), and the urinary score of the PFDI‐20 questionnaire decreased from 31.4 ± 17.9 preoperatively to 9.3 ± 12.3 postoperatively ( P  < 0.001). Furthermore, 15 (51.7%) women reported complete resolution of UI following weight loss. Conclusion: Surgically induced weight loss resulted in resolution of UI in up to 52% of preoperatively incontinent women and subsequent improvement in other pelvic floor symptoms. Larger studies with longer follow‐up are required to investigate the possible impacts of bariatric surgery on various aspects of pelvic floor function. Neurourol. Urodynam. 36:184–187, 2017 . © 2015 Wiley Periodicals, Inc.